2016
DOI: 10.1063/1.4967285
|View full text |Cite
|
Sign up to set email alerts
|

Engineering perpendicular magnetic anisotropy in Fe via interstitial nitrogenation: N choose K

Abstract: In this work, combining experimental results and first principles calculations, we show that interstitial nitrogen not only serves for inducing tetragonality in α′-Fe8Nx but is also essential for achieving a high degree of perpendicular magneto-crystalline anisotropy, K. Our results demonstrate that the orbital magnetic moments of the iron atoms above and below N in the direction of magnetization are much more susceptible to the applied magnetic field than their in-plane counterparts, leading to a giant value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The change in crystallographic symmetry can affect the magnetic anisotropy in such regions. For instance, several studies have reported that an increase of tetragonality in Fe, supported by interstitial nitrogen atoms, can increase the magnetic anisotropy energy [50][51][52][53]. Theoretical studies explain that the tetragonality in Fe stabilizes orbital magnetic moments and enhances the magnetic anisotropy via spin-orbit coupling [53,54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in crystallographic symmetry can affect the magnetic anisotropy in such regions. For instance, several studies have reported that an increase of tetragonality in Fe, supported by interstitial nitrogen atoms, can increase the magnetic anisotropy energy [50][51][52][53]. Theoretical studies explain that the tetragonality in Fe stabilizes orbital magnetic moments and enhances the magnetic anisotropy via spin-orbit coupling [53,54].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, several studies have reported that an increase of tetragonality in Fe, supported by interstitial nitrogen atoms, can increase the magnetic anisotropy energy [50][51][52][53]. Theoretical studies explain that the tetragonality in Fe stabilizes orbital magnetic moments and enhances the magnetic anisotropy via spin-orbit coupling [53,54]. Although voids and impurity nanoparticles may be regarded as the pinning points with respect to the motion of the magnetic domain walls [55], no shoulder can be observed in the case of residual scattering at 10 T, indicating that HPT-Fe is likely to contain few such nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting question is how such tetragonal distortions can be stabilized. We suspect that light interstitial atoms such as H, B, C, and N will lead to substantial tetragonal distortions, as recently investigated in Fe [61] and FeCo [62,63] alloys. Systematic calculations have been performed on compounds with the Cu 3 Au (as for Mn 3 Pt) and Heusler (as for Mn 2 RhPt and Fe 2 CoGa) structures with light interstitials, and the results will be reported elsewhere.…”
Section: Tetragonally Distortion Of Cubic Phasesmentioning
confidence: 79%
“…Finally, concerning the cubic phases in which a tetragonal distortion can induce a large MAE (see Section 4.2.2), we think that adding light interstitial atoms such as H, B, C, and N in these compounds might be a likely way to achieve it in practice [61,62,63]. Figure 18: Strategy to make use of Novamag database for tuning Fe 3 Sn phase.…”
Section: Possible Strategies To Exploit Promising Theoretical Novel Pmentioning
confidence: 99%
“…In recent years, major effort has been made to search for the RE-free PM materials [6]. The reason is a growing concern for the RE elements' (Nd, Sm, Dy) sustainability, together with growing demand from the industry for cheap and stable high-temperature PMs [2].…”
Section: Introductionmentioning
confidence: 99%